Some effects on oak-feeding insects of seasonal changes in the nature of their food - Feeny, P (1966)
The present work has been restricted to an investigation of the relationship between the leaves of the common oak Quercus robar L. and the larvae of the order Lepidoptera which feed on them. At least 210 species of Lepidoptera have been recorded as larvae feeding on oak leaves in Britain and there is evidence that insect growth and survival on young oak leaves may be higher than on the leaves of other species. More species and higher numbers of Lepidoptera larvae are found on oak leaves in April and May than in any other months of the year and there is evidence, from the high mortality of young winter moth Operophtera brumata L. larvae due to premature hatching , that there may be strong selection pressure for early larval feeding in this species. It is unlikely that predation or parasitism are responsible for this selection pressure and it was suspected that the concentration of larval feeding in the spring might be due to changes in the nature of the oak leaves as the season progresses. This thesis describes some investigations into the seasonal variation of the toughness, nutrient content and tannin content of oak leaves and into the possible effects which these factors might have on caterpillar growth and subsequent insect survival. Fieldwork was largely carried out in Wytham Wood, near Oxford. The caterpillar populations on the leaves of one oak tree were sampled during the spring of 1964. Although the number of caterpillars in May and June was greater than 200/sq.m., very few larvae could be found on the leaves after mid-June. The winter moth was selected for laboratory study. It was found that winter moth larvae which had been fed on oak leaves, collected in late May and early June, reached very much lower peak and pupal weights than larvae which had been fed on leaves collected in mid-May. Adult emergence from the pupae resulting from larvae fed on the early leaves was about 50% whereas no adults emerged from pupae resulting from larvae fed on the later leaves. This shows that a difference of only 12 days in leaf age can significantly affect larval growth, pupal weights and adult emergence. The toughness of oak leaves collected in June, measured with a specially constructed device, was found to be considerably greater than that of leaves collected in May. The effect of leaf toughness on the fresh weight increase of winter moth larvae was investigated by rearing larvae on two agar diets, each containing a finely ground powder derived from May and June oak leaves, respectively. It was found that the larvae fed on the June leaf powder diet increased in weight at almost the same rate as the larvae reared on the May leaf powder diet. This result, in conjunction with that from the previous experiment, suggests that leaf toughness may be important in determining the ability of winter moth larvae to grow satisfactorily on oak leaves. It is considered unlikely, however, that increase of leaf toughness can adequately account for the evident selection pressure favouring early larval feeding. If leaf toughness was the only barrier preventing late feeding, stronger larval mandibles would probably have been evolved, as has happened in some species which do feed on older leaves. Analyses were carried out on the leaves of one oak tree to determine the seasonal variation of sugar content. It was found that variation in the concentration of reducing sugars (glucose and fructose) in the leaves followed no obvious trend during the growing season) though sucrose concentration increased rapidly during early June and remained at a level of about 6% (dry weight of leaf) during the summer months. The sugar content of oak leaves is therefore lower during April and May than during other months of the year. For this and other reasons, such as the apparent lack of an amylase enzyme in the winter moth, it was considered that the growth of winter moth larvae is normally not limited by the level of carbohydrates in oak leaves. Analyses were carried out on the leaves of six oak trees to determine the seasonal variation of total nitrogen content. It was found that the 'protein' content of the leaves (calculated as total nitrogen x 6.25) is high in buds and young leaves (about 30% dry weight of leaf), but drops rapidly to about half this value by the end of May and then remains steady at about 12% dry weight of leaf at least until September. There is therefore a correlation between early larval feeding periods and a high nitrogen content of the leaves, which may suggest that total nitrogen, or the concentration of certain nitrogenous compounds, may be important in determining the optimum feeding times for Lepidoptera larvae. Oak leaves have been known for centuries to contain tannins. Tannins are known to have biological effects, including inhibition of fungal growth and virus infection, which are believed to be due to the ability of tannin to form complexes with proteins. It was considered possible that the presence of tannins in oak leaves might have an adverse effect on the growth and survival of caterpillars, either by directly inhibiting digestive enzymes or by reducing the availability of leaf protein to insect digestion. The phenolic compounds of oak leaves were investigated during the growing season by means of two-way paper chromatography. The most obvious seasonal change was found to be the appearance of condensed tannin, and its probable precursors (+)-catechin and (+)-gallo-catechin, in the leaves at the end of May and the apparent increase in concentration of condensed tannin in the leaves during subsequent months. Tannins were isolated from oak leaves tgr an ether-precipitation method. The crude tannin material war, found to contain at least one hydrolysable component, in addition to the condensed tan in, The crude material was eventually separated into the two major components (condensed tannin and hydrolysable tannin) by Sephadex column chromatography, followed by purification on thick paper. Quantitative analysis of the leaves of one oak tree showed that the concentration of tannins in the leaves increases from about 0.5% dry weight in April (when only hydrolysable tannin is present) to about 5% dry weight in September (when both hydrolysable and condensed tannins are present). The analyses were carried out by a gravimetric adaptation of the ether-precipitation method, previously used for isolating tannins. However, a new spectrophotometric method for the rapid determination of condensed tannin in leaf extracts was subsequently devised. Effects of oak leaf tannins on the fresh weight increase and pupal weight of winter moth larvae were investigated by rearing larvae on artificial diets, to which crude oak leaf tannins were added. Although the experiments were marred by mortality, due to fungus, virus and microsporidian infections, the results nevertheless clearly showed that larval fresh weight increase and pupal weight are reduced by the presence of tannin in the diet. It is considered likely that reduction in larval peak weight and pupal weight is an indication of a potential adverse effect on subsequent adult weight and fecundity, though this was not proved, owing to the high mortality. Several in vitro experiments were carried out to determine the ability of oak leaf tannins to form complexes with casein (the protein incorporated in the artificial diet experiments) and leaf protein (from nettle leaves). It was found that both protein preparations were completely complexed at pH 5.0 by their own weights of oak leaf tannin and probably by lower quantities of tannin. Oak leaf tannin was found to inhibit almost completely the hydrolysis of starch by α-amylase at pH 6.0. Moreover, digestion, of casein by mammalian trypsin was almost completely inhibited at pH 7.6. There is evidence that tannin-protein complexes are dissociated to some extent under alkaline conditions. The effect of hydrolysable and condensed oak leaf tannins on the hydrolysis of casein and nettle leaf protein was therefore determined separately at pH 9.2, found by two methods to be the pH of the winter moth mid-gut. It was found that inhibition of hydrolysis at this pH was much less pronounced than at pH 7.6, indicating some dissociation of the complexes in the mid-gut. Hydrolysable tannin was found to have little effect on the hydrolysis of either protein, but a concentration of condensed tannin equivalent to only 30% of the concentration of the casein reduced the hydrolysis of this protein by about 50%. Condensed tannin is therefore much more effective as an inhibitor of protein hydrolysis than is hydrolysable tannin. This is of interest in view of the different seasonal occurrence of these two tannins, already mentioned. It is possible that one of the functions of the high mid-gut pH found in many phytophagous larvae, may fee to increase the availability of protein by partial dissociation of protein-tannin complexes. It was found by autoradiography that 14Carbon labelled Chlorella vulgaris protein can be incorporated into the mid-gut tissues of the winter moth in the presence of oak leaf condensed tannin, though the protein, on account of its denatured condition, was not initially present as a tannin-protein complex. Both condensed and hydrolysable tannins were labelled with 14Carbon by enclosing oak leaves in situ in an atmosphere containing labelled carbon dioxide. These labelled tannins were fed to winter moth larvae to determine by autoradiography the fate of tannins in the larval mid-gut. This experiment is still in progress. It was concluded from the experiments described in this thesis that oak leaf tannins might have an adverse effect on larval growth and survival in the field, by reducing the availability of leaf nitrogen for larval digestion. It was estimated that the concentration of protein in oak leaves which is available for insect growth might be about five times higher in April than it is in September. It is not known to what extent this effect may be responsible for the evolution of early feeding periods for the larvae of many Lepidoptera species. The increase in the tannin content of oak leaves does not seem to be sufficiently rapid to account for the evident strength of the selection pressure favouring early feeding by winter moth larvae and it is possible that other factors, such as the availability of micronutrients, might be important. However, it is also possible that even small concentrations of tannins in oak leaves might have much greater effects on insect survival under natural conditions than have been indicated by the laboratory experiments.